If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -6) = 42 Reorder the terms: 2(-6 + x) = 42 (-6 * 2 + x * 2) = 42 (-12 + 2x) = 42 Solving -12 + 2x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 2x = 42 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = 42 + 12 2x = 42 + 12 Combine like terms: 42 + 12 = 54 2x = 54 Divide each side by '2'. x = 27 Simplifying x = 27
| (4x+1)-7=22 | | 13+(2-x)=-6 | | 2x-2=110 | | 6x+23=16x-97 | | 5(x+6)-17= | | 2x-(5)=4x-(1) | | X^2+2kx+4k=0 | | 12x-8=-56 | | x+3y=360 | | -5(8n+3)= | | 6x+6=3x+33 | | 10+7x+52=x | | 21x+1+53=180 | | 5x+10=-5 | | 11-9x=104-30x | | 9x^2-121= | | 2z+7z+5z-1= | | 4x+32=11x-94 | | y^4-2y^2-8=0 | | 3x-6x+5x-9x= | | (x*5)+(.1x*15)=3260 | | 6x-3-2x=17 | | (48-3)/5=x | | s=.5gt | | 9(q+2)= | | 5e+8=56 | | 4x=11-3 | | 7x-4=-2x+1+9 | | 5(7y)= | | 3x+34=6x+10x | | (3x-3)+(3x-3)+(x-3)+(x-3)=(2x-1)+(2x-1)+(2x) | | 2x-6x+7x-5x= |